Viral Genetic Determinants of H5N1 Influenza Viruses That Contribute to Cytokine Dysregulation - Mok, Ka Pun (2009)
Human disease caused by highly pathogenic avian influenza (H5N1) is associated with fulminant viral pneumonia and mortality rates in excess of 60%. Cytokine dysregulation is thought to contribute to its pathogenesis. In comparison with human seasonal influenza (H1N1) viruses, clade 1, 2.1, and 2.2 H5N1 viruses induced higher levels of tumor necrosis factor-α in primary human macrophages. To understand viral genetic determinants responsible for this hyperinduction of cytokines, we constructed recombinant viruses containing different combinations of genes from high-cytokine (A/Vietnam/1203/04) and low-cytokine (A/WSN/33) phenotype H1N1 viruses and tested their cytokine-inducing phenotype in human macrophages. Our results suggest that the H5N1 polymerase gene segments, and to a lesser extent the NS gene segment, contribute to cytokine hyperinduction in human macrophages and that a putative H5 pandemic virus that may arise through genetic reassortment between H5N1 and one of the current seasonal influenza viruses may have a markedly altered cytokine phenotype.